OPTIMAL ENFORCEMENT OF NONCOMPETE COVENANTS. (5th May 2016) - Ghosh, Suman; Shankar, Kameshwari
Abstract : Noncompete covenants or covenant not to compete (CNC) are clauses in employment contracts in which the employee agrees not to gain employment with a competitor firm. In this article, we study the efficiency aspects of such contracts by incorporating the effect of labor mobility restrictions on knowledge transfer across firms, investment decisions by firms, and investment by workers. Following research that shows state‐wise variations in the degree of CNC enforcement, we allow the strength of CNC enforcement to vary as a matter of regulatory policy and derive the optimal strength of enforcement. We also look at how regulations around CNCs should be optimally designed when employers can use collusive agreements, such as "no poaching" agreements, as an alternative to noncompete clauses. Given recent allegations of employer collusion among large Silicon Valley firms, we argue for a cautious approach in designing policies on CNC enforcement. ( JEL J24, J41, J63, K31)